Epidemiological behavior of diabetes mellitus in a family physician's office - Eduardo Enrique Chibas Muñoz; Sheyla María Herrera Ortega; Erennys Carema Sarabia Aguila; Rogelio Creagh Bandera (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: diabetes mellitus is a metabolic disease characterized by hyperglycemia, due to defects in insulin secretion, insulin action or a combination of both; genetic factors and changes in the dietary pattern are involved in its presentation. Objective: to describe the epidemiological behavior in patients diagnosed with diabetes mellitus. Method: an observational, descriptive and transversal study was carried out in the office of family doctor number 4 belonging to the Mártires del 4 de Agosto polyclinic of the municipality of Guantánamo, Guantánamo province, in the period from January to June 2021, with a total of 191 patients diagnosed, working with all of them. In the statistical analysis, variables such as age, sex, smoking and alcoholism history, physical activity and body mass index were used. The SPSS 23.0 statistical package was used to obtain descriptive indicators, as well as totals and percentages. Results: patients over 60 years of age were predominant (48.1%), the average age was 58 years, the predominant sex was female (58.1%), diabetes mellitus type 2 was representative (54.5%), as for physical activity, sedentary patients accounted for 83.8%. Conclusions: patients older than 60 years of age, type 2 diabetics, of the female sex were the most predominant in the population studied. Patients with a history of smoking as a toxic habit and sedentary physical activity were representative.